The first documentation of the immune response to cutaneous leishmaniasis caused by Leishmania donovani in Sri Lanka. - D. Atapattu; D. Iddawela; S. Adikari; S. Wickramasinghe; L. Bandara; S. Samaraweera (Sri Lankan Journal of Infectious Diseases, 2017)
Introduction and Objectives: The predominant form of leishmaniasis seen in Sri Lanka is cutaneous leishmaniasis (CL) caused by Leishmania donovani, a species commonly causing visceral disease. The objective of this study was to explore the human host immune response to CL in Sri Lanka.   Methods: A descriptive comparative study was carried out on nine CL patients referred to the Department of Parasitology, Faculty of Medicine, University of Peradeniya, Sri Lanka, during 2011-2013. mRNA was extracted from the skin biopsy samples and reverse transcribed to cDNA and tested for Th1 and Th2 cytokines by using specific primers for IFN-γ, IL-2 (Th1 cytokines) and IL-4, IL-10 (Th2 cytokines). The results were compared with different characteristics of the lesion (number, duration, size and type of lesion).   Results: This study revealed that the majority of CL patients (5/9) elicited a Th1 response whereas a Th2 response was not detected in any of the patients. Of the Th1 cytokine positive patients, majority had single lesions, with a shorter duration and smaller sized lesions which were of the plaque type. Of those which exhibited a negative Th1 response, the majority were larger lesions with a longer duration and were of the papular-nodular type.   Conclusions: The study suggests that the predominant immune response to CL caused by L. donovani in Sri Lanka, is a Th1 type of response which may explain the localization of L. donovani which is usually a viscerotropic species, to skin tissue.   Limitations of study: This study was done only in nine patients due to resource limitations. A continuation of this study is indicated to validate these results.